POLA PENGEMBANGAN POTENSI KECERDASAN EMOSIONAL DAN SPIRITUAL ANAK PENYANDANG AUTISME - Zainal Abidin; Isti Fatonah; Linda Septiyana (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2019)
This research is a qualitative field research which attempts to analyze the development of emotional and spiritual intelligence of Autism Persons at Autism Service Center (PLA) Metro. This study seeks to answer the question of how the pattern of developing emotional intelligence and spiritual intelligence of children with autism inpla Metro. To make it easier to answer and find the research question, in this study using several methods including direct observation, in-depth interviews, and studying documentation based on data obtained in the field. The results of this study indicate that the pattern of development of emotional intelligence and spiritual intelligence of children with autism is indeed somewhat different from normal children, even between autistic one with autism, because it turns out there are differences in the types of autism itself. In general, the pattern of intelligence development of autistic children requires special handling, by combining it with several well-known therapeutic methods in the handling of autism such as the ABA (Applied Behavior Analysis) method, physiotherapy, speech therapy, out door therapy, and others. The therapy method is combined with a religious approach to get emotional and spiritual intelligence, by getting used to autism and at the same time the therapist always prays in starting his therapeutic activities. This habituation is a reflection of the awareness of the